Influence of the per pulse laser fluence on the optical properties of carbon nanoparticles synthesized by laser ablation of solids in liquids - Reyes-Contreras, Delfino; Camacho-López, Marco; Camacho-López, Miguel A.; Camacho-López, Santiago; Rodríguez-Beltrán, René I.; Mayorga-Rojas, Miguel (Optics and laser technology, 2015)
In this work we present experimental results on the optical characterization of carbon-nanoparticles (CNPs) synthesized by the laser ablation of solids in liquids technique (LASL). A pulsed Nd-YAG laser, a graphite disk and acetone were used in the laser ablation experiments. The per pulse laser fluence was varied, while all the other irradiation parameters (irradiation time, repetition rate, etc.) were kept constant. Both the graphite target and the obtained CNPs were characterized by Raman micro-spectroscopy. The colloidal solutions were characterized by UV–vis and photoluminescence (PL) spectroscopies. Additionally, the CNPs were also characterized by TEM and HRTEM. Our results show that spherical nanoparticles in the range of 4–20nm in diameter were obtained. UV–vis and PL results for the obtained CNPs colloidal solutions showed that the optical absorption and PL intensity are dependent on the per pulse laser fluence. We also found that the PL spectral emission of the CNPs can be tuned from blue to yellow by varying the excitation wavelength. •LASL is a simple and fast technique to obtain CNPs colloidal solutions.•CNPs colloidal solution PL intensity depends on the per pulse laser fluence.•The PL of CNPs prepared by LASL is tunable for different excitation wavelength.